Irrigation effects on aromatics and phenolics of eggplant (Solanum melongena) - Eylem Polat, Havva; Zambi, Ozan; Güçer, Yalçın; Serdar Anli, Alper (Italian Journal of Food Science, 2024)
This research examines the impact of treated and untreated wastewater on eggplant cultivation, focusing on the aroma profile and phenolic composition. The results demonstrate significant alterations in dry matter content, pH levels, and total phenolic compounds in eggplant varieties irrigated with wastewater, compared to tap water. Regarding total phenolic content, the highest result was 120.14 mg kg–1 in the Kemer variety irrigated with wastewater. The amount of water-soluble dry matter in eggplant varieties irrigated with physical treatment (WW1), physical + biological treatment, and municipal (tap) water (MW) was found to vary between 7.80% and 5.20%. The aromatic analysis identifies variations in volatile compounds with higher concentrations of specific components, such as farnesene (30.60%), benzene (22.05%), and non-(2E)-enal (26.89%), under different qualities of water irrigation treatments. An increase in the purification level of irrigation water increased the percentage of farnesene , ranging from 15.13% (Aydın Siyahi, WW1) to 30.60% (Kemer, MW). The results underline the importance of sustainable water management practices and highlight the need to quality of irrigation water in agricultural areas to ensure soil health, environmental sustainability and food safety.